2013
DOI: 10.1186/1741-7015-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Novel aspects of Sjögren’s syndrome in 2012

Abstract: Sjögren’s syndrome (SS) is a systemic progressive autoimmune disease characterized by a complex pathogenesis requiring a predisposing genetic background and involving immune cell activation and autoantibody production. The immune response is directed to the exocrine glands, causing the typical ‘sicca syndrome’, but major organ involvement is also often seen. The etiology of the disease is unknown. Infections could play a pivotal role: compared to normal subjects, patients with SS displayed higher titers of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 115 publications
1
143
0
4
Order By: Relevance
“…According to Tincani et al, 33 pSS patients present a progressive impairment of the salivary glands, with consequent decrease in salivary flow. In the present study, there was an improvement in the salivary flow of pSS patients at 30 and 90 days after periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tincani et al, 33 pSS patients present a progressive impairment of the salivary glands, with consequent decrease in salivary flow. In the present study, there was an improvement in the salivary flow of pSS patients at 30 and 90 days after periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…SS is the second most common autoimmune rheumatic disease [2], with a prevalence of approximately 1% (range 0.1-4.8%) [2,4] and an incidence of about 7 per 100,000 person-years at risk [5,6]. In total, up to 4 million Americans have SS [7][8][9].…”
Section: Epidemiology Of Ssmentioning
confidence: 99%
“…A large study of 327 patients presenting with clinically significant aqueous-deficient dry eye (ADDE) in the US found 11.6% of the patients to have SS [3]. Salivary gland dysfunction leads to dry mouth and associated problems such as trouble swallowing dry food, dental caries, and even oral candidiasis [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 It has also been found that environmental and hormonal factors, the fatsoluble vitamins such as vitamin D, may have a role in the pathogenic immunoregulatory process of primary Sjögren's syndrome (Pss). [4][5][6] The vitamin D supplementation is suggested for chronic autoimmune diseases. 4 Low levels of vitamin D may be related with low-complement components and the presence of cryoglobulins in predicting eventual development of lymphoma in patients with Ss.…”
Section: Introductionmentioning
confidence: 99%